1.1-4x-3.1-2x=-5x-3.3

Simple and best practice solution for 1.1-4x-3.1-2x=-5x-3.3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 1.1-4x-3.1-2x=-5x-3.3 equation:


Simplifying
1.1 + -4x + -3.1 + -2x = -5x + -3.3

Reorder the terms:
1.1 + -3.1 + -4x + -2x = -5x + -3.3

Combine like terms: 1.1 + -3.1 = -2
-2 + -4x + -2x = -5x + -3.3

Combine like terms: -4x + -2x = -6x
-2 + -6x = -5x + -3.3

Reorder the terms:
-2 + -6x = -3.3 + -5x

Solving
-2 + -6x = -3.3 + -5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '5x' to each side of the equation.
-2 + -6x + 5x = -3.3 + -5x + 5x

Combine like terms: -6x + 5x = -1x
-2 + -1x = -3.3 + -5x + 5x

Combine like terms: -5x + 5x = 0
-2 + -1x = -3.3 + 0
-2 + -1x = -3.3

Add '2' to each side of the equation.
-2 + 2 + -1x = -3.3 + 2

Combine like terms: -2 + 2 = 0
0 + -1x = -3.3 + 2
-1x = -3.3 + 2

Combine like terms: -3.3 + 2 = -1.3
-1x = -1.3

Divide each side by '-1'.
x = 1.3

Simplifying
x = 1.3

See similar equations:

| 2(4z+4)-9=39 | | 2x+4y=106 | | (x*x)-6x=0 | | 92*67*67*67*98*75*57*23*34= | | 5y+6=6y-14 | | 2/5b-6-2 | | ln(3x-18)=8 | | 2(2x+2)=4x+6-2 | | (x^2-5)(x^2-4x+5)=0 | | 12x+12-x-5=92 | | 106=41(2x+4y) | | 5+x=87 | | 2-k=0 | | 2(x^2-5)(x^2-4x+5)=0 | | a^2+a+a^2=0 | | 36/3/5 | | 155.00x+7500.00=92440.00 | | X*2+5=-14 | | 39.55+0.20m=80 | | x^(2/3)-1 | | 15+3=18y | | 5b+3(4+5b)= | | x^2=7-2x | | 2x^7-16x^6+12x^5= | | 5+3(4+5)= | | (-15/2)(-1) | | 7x+1x=28+9x | | (324*80)= | | 2x^4-8x^3+40x-50=0 | | 7x+1x=14+9x | | 2.583+(-5.399)= | | 7x+1x=28+9 |

Equations solver categories